Principles of lightware communications - Einarsson, Goran (John Wiley & Sons, 1996)
Principles of Lightwave Communications Göran Einarsson Royal Institute of Technology, Stockholm, Sweden Advances in optical communications and optoelectronic components have revolutionized telecommunication transmission. Uniquely, this book provides a comprehensive treatment of optical fiber communications using a modern communication theory approach. Presenting mathematical models for the building blocks of optical systems, this authoritative text provides a solid basis for analysis and design of lightwave communications systems.